A holistic X-ray analytical approach to support sensor design and fabrication: Strain and cracking analysis for wafer bonding processes. (15th November 2021) - Borzì, A.; Zboray, R.; Dolabella, S.; Le Neal, J.F.; Drljaca, P.; Fiorucci, G.; Dommann, A.; Neels, A.
Graphical abstract: Highlights: Silicon-to-sapphire wafer bonding through an innovative method and characterized by high-resolution XRD and X-ray micro-CT. The innovative silicon-to-sapphire wafer bonding proved effective and strong opening the floor to a remarkable advancing in packaging design. X-ray micro computed tomography revealed powerful for quantifying 3D-volume defects in mm-thick structures and assess the bonding process effectiveness. A comprehensive understanding of the degradation mechanisms acting at the micron/nano-scale is only accessible by a conjoint X-ray-based approach. The approach demonstrated applies to the quantitative analysis of the status of materials involved into each partially destructive microfabrication process. Abstract: Devices such as sensors, actuators, or micro-electromechanical systems (MEMS) are obtained by a variety of microfabrication processes. Many of these processes influence the material systems by the introduction of strain and defects, which may affect the final device's performance and reliability. Indeed, controlling materials' status during the microfabrication is fundamental for the process optimization itself and for guaranteeing the highest devices performances during their lifetime. In this work, a conjoint analytical approach between high-resolution X-ray diffraction (HRXRD) and X-ray micro-computed tomography (CT) evaluates an innovative silicon-to-sapphire wafer bonding process. Large cracks 30–60 µm-thick were identified in both crystals by micro-CT and related to the interfacial high-stress release. In parallel, a multi-domain microstructure associated with strain and tilt affect the silicon crystallinity due to smaller cracks and defects which originate at the bonding interface and travel to the outer part of the crystal. The effectiveness of the bonding is also assessed by our approach and further enforced by means of SEM observation of the sample cross-section. Here, a unique approach by combining X-ray micro CT with HRXRD for a holistic evaluation of silicon-to-sapphire wafer-bonding processes and correlate the micrometer scale and volumetric defect detection (voids and cracks) with atomic-level strain and defect analysis is presented.